Evaluación de la capacidad de autodepuración de materia orgánica del río carrizal sobre los efluentes de la laguna de oxidación de Calceta - Flores Pinargote, José Alfredo (2020)
This research work helped to identify the problem as true to reality as posible which is a problem for the Carrizal River, especially for those who use the wáter resource for their daily activities. The self-purification capacity is one of the factors that influences the water quality of the Carrizal River. To do this, various physical chemical parameters such as flow, pH, temperature, dissolved oxygen and organic matter were carried out. The monitoring was carried out according to the Monitoring Protocol of the Water Resources of Peru where 4 points were taken after the discharge, the point of discharge and a white point as a reference in the dry season of 2019 in the months of (September, October and November). To define these monitoring points, a primary tour of the study área was made and with the ArcGis v10.4.1 software, a georeferenced map could be made. The monitoring was done in dry season. Samples of organic matter were carried out in the environmental chemistry laboratory of ESPAM MFL and the rest of the parameters were carried out with the help of instruments such as potentiometer and oximeter. Once the tabulation was completed, the data was entered into the Excel v14.0 software with the Stretter-Phelps model, which projected that the Carrizal river removed 23,76% of organic matter, from the mixing point with the discharge to the 9000 meters with a decrease of 7,28 mg / l to 5,52 mg / l.